Increasing self‐drinking for children with feeding disorders. Issue 2 (1st May 2015) - Peterson, Kathryn M.; Volkert, Valerie M.; Zeleny, Jason R.
<x xml:space="preserve">Abstract</x> Children with feeding disorders often do not self‐drink without treatment. Unfortunately, the literature on self‐drinking is scarce. We evaluated differential positive reinforcement to increase self‐drinking for 2 children with feeding disorders. Results showed that differential positive reinforcement with tangible items increased self‐drinking for both children in the absence of nonremoval of the cup.